A superlinguistics of hyperlink ‘pointing’ - Kuhn, Jeremy; Lorin, Louis-Marie (Proceedings of Sinn und Bedeutung, 2021)
We present a ‘superlinguistic’ analysis of hyperlinks, building on parallels with cospeech pointing gestures. We show that one is able to give acceptability judgments for hyperlink placement and use, allowing us to define a precise syntax and semantics of hyperlinks. We show that these patterns interact with core linguistic systems, including constituent structure, semantic type, veridicality, and information structure.